SIFAT FISIKO KIMIA MINYAK CUPRESUS (Cupressus benthamii) ASAL AEK NAULI, PARAPAT SUMATERA UTARA - Santiyo Wibowo; Sri Komarayati (Jurnal Penelitian Hasil Hutan, 2015)
This paper studies the characteristic of cupressus oil (Cupressus benthamii Endl) from Forestry Research Institute Arboretumat Aek Nauli. The essentialoil colected fromleavesof Cupressus benthamii plant bysteam distilation of a fresh and dry leaves for seven hours. Result shows that the dry leaves provide the highest yield (0.41%) with its properties of specific gravity 0.889, refractive index 1.481, solubility on ethanol 1:5, and acid value 3.8 mg KOH/g sampel. The chemical compound of cupressus oil was dominated by ɑ-pinene (17.6%), sabinene (8.59%), 4-terpineol (6.56%), and ϒ- terpentin (5.12%).